2023
DOI: 10.1097/bot.0000000000002520
|View full text |Cite
|
Sign up to set email alerts
|

Financial Toxicity Is Common in Patients After Tibia Fracture

Abstract: Setting: Level I trauma center.Patients: All patients within 4 years after tibial shaft fracture (open, closed, or fracture that required flap reconstruction).Intervention: Injury-related financial distress.Main Outcome Measurements: Financial distress related to the injury, as reported by the patient in a binary question. Financial toxicity using the LIMB-Q, scored from 0 to 100, with higher scores indicating more financial toxicity.Results: Data were collected from 142 patients after tibial shaft fracture [4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The nancial toxicity of patients with PD-related complications was higher than that of patients without PD-related complications. Lily R. Mundy [31] investigated nancial toxicity in 142 patients with tibial shaft fractures and found that medical complications were associated with increased nancial toxicity, similar to the results of this study. PD-associated peritonitis is the most common infectious complication of PD and is associated with several negative clinical consequences, including hospitalization, increased health care utilization and costs, associated mortality and peritoneal changes [32].…”
Section: Discussionsupporting
confidence: 80%
“…The nancial toxicity of patients with PD-related complications was higher than that of patients without PD-related complications. Lily R. Mundy [31] investigated nancial toxicity in 142 patients with tibial shaft fractures and found that medical complications were associated with increased nancial toxicity, similar to the results of this study. PD-associated peritonitis is the most common infectious complication of PD and is associated with several negative clinical consequences, including hospitalization, increased health care utilization and costs, associated mortality and peritoneal changes [32].…”
Section: Discussionsupporting
confidence: 80%
“…The high prevalence of financial distress after injury has been previously reported. 21,25 However, some pa-tients described how they were largely protected from financial toxicity after their injury. Based on our analyses, avoiding financial distress after an injury is likely attributable to one of three different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The interview guide was informed by an extensive literature review to provide the basic direction. 6,7,[16][17][18][19][20][21][22][23][24][25][26] The questions explored the participants' current experience with financial distress, its effect on their postoperative recovery decisions, and the support they had sought or received to mitigate this financial distress (Supplemental Appendix, Interview Questions, http://links.lww.com/ JAAOS/B25).…”
Section: Data Collectionmentioning
confidence: 99%